PERLINDUNGAN HUKUM BAGI PEMEGANG HAK ATAS TANAH DALAM KASUS TUMPANG TINDIH KEPEMILIKAN HAK ATAS TANAH DIWILAYAH SAMOTA KABUPATEN SUMBAWA - ARIEF RAHMAN; WIWIEK WAHYUNINGSIH; SHINTA ANDRIYANI; DIMAN ADE MULADA (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to examine and analyze related to overlapping ownership of land rights in the Samota area, Sumbawa Regency and the role of the land office of Sumbawa Regency in addressing land dispute cases in terms of overlapping ownership of land rights. The type of research used in this article is normative research. and empirically using the statutory approach, conceptual approach, case approach, and sociological approach.The results showed that the factors causing overlap of land ownership rights in the Samota area, namely: Land registration under 2005 related to the determination of coordinates is still done manually, in contrast to the current determination of coordinates for land registration. using systemized technology, landowners do not pay attention to their land and do not use it properly so that it is taken over by other people and then used because they feel that the land is no owner or has no owner. Feeling that he has owned the land for a long time, the person then claims that the land is his and issues a certificate on the land. The sub-district or village does not have data on land that has been certified and has control over it, so it is easy to issue a certificate land tenure, etc., the land owner resubmits the application for the issuance of a replacement certificate on the grounds that the certificate is lost, even though previously the land he owned had been transferred to another party. As well as the role of the Sumbawa District Land Office in Providing Legal Protection Against Cases of Overlapping Land Ownership Rights in the Samota Region, namely by facilitating the disputing parties to find solutions related to resolving disputes over overlapping ownership of land rights. The form of facilitating the disputing parties related to overlapping ownership of land rights by the Sumbawa Regency Land Agency office is carried out by means of mediation